Notary’s Responsibility in Making of Deed Due to Land Acquisition Containing Criminal Corruption - Yogi Maron; Ismansyah Ismansyah; Azmi Fendri (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
As happened to the Notary Eli SatriaPilo, S.H, Mkn, who was appointed as the Notary who made the Deed of Relinquishment of Land Rights in the Land Acquisition activities for the Construction of Campus III of the State Islamic Institute (IAIN) of Padang which was located in Sungai Bangek District, Padang in 2010. The method used was descriptive, in which describing the applicable legislation associated with legal theory in the facts and realities about the Notary’s Responsibility in Making Deed of Land Acquisition for the construction of Campus III of IAIN Padang in Sungai Bangek. This study used a Normative Juridical approach, in which researching by using and processing secondary data or literature related to the study. The data collected were in the form of primary data obtained from the District Court of Padang, secondary data obtained from secondary legal materials and primary legal materials. Based on the study, it was found that the role of Notary Eli Satria Pilo, in the land acquisition of campus III IAIN was proven to have misused the authority resulting in violation of the Notary Ethics Code and was responsible for accepting termination disrespectfully. Furthermore, he was also shown to be committing a Criminal Corruption made based on the Deed of Relinquishment of Land Rights in the land acquisition for the construction of Campus III of IAIN Padang, so that the State incurred losses of Rp. 1.946.701.050 (one billion nine hundred forty-six million seven hundred one thousand and fifty rupiahs). And he was responsible for receiving and carrying out the sentence that had been handed down by the District Court of Padang, a prison sentence of 4 (four) years, and paying a fine of Rp. 200.000.000 (two hundred million rupiahs).